Diversifikasi Dan Peningkatan Mutu Organoleptik Selai Nanas Melalui Formulasi Inovatif Pada Umkm Radja Nanas Bantaeng - Andi Hermina Julyaningsih; Andi Nur Faidah Rahman; Ibnu Mansyur Hamdani; Wiwin Reski Windarsari (Abdi Techno, 2026)
Radja Nanas MSME is a local enterprise in Bantaeng Regency engaged in the cultivation of pineapple (Ananas comosus (L.) Merr.) and the production of its processed products. One of its leading products is pineapple jam. However, the organoleptic quality of the pineapple jam produced by this MSME still requires improvement, particularly in terms of color and texture. The resulting jam tends to have a darker color, and its consistency is excessively thick compared to commercial pineapple jam standards. In addition, the selling price of the product is relatively high and lacks variation, as the jam formulation relies solely on pineapple without incorporating other potential raw material substitutions that could enhance product quality and market value. This community service program aimed to diversify pineapple jam products and improve their organoleptic quality, enabling Radja Nanas MSME to introduce new product variants with enhanced quality and greater consumer acceptance. The implementation methods included the transfer of appropriate technology in the form of an automatic jam stirrer to improve both production quality and quantity. Furthermore, educational sessions were provided on proper jam-processing techniques to ensure the production of high-quality pineapple jam. Finally, hands-on training was conducted to develop new pineapple jam variants by incorporating dragon fruit, papaya, and carrot into the formulation. This innovation was intended to enhance organoleptic properties and nutritional value while simultaneously reducing production costs. The community service activities were successfully implemented, marked by the delivery of the automatic jam stirrer to Radja Nanas MSME. Moreover, there was a measurable improvement in participants’ knowledge regarding proper pineapple jam processing methods and the development of three new pineapple jam variants.